The Effect of Psychological Empowerment in Achieving Organizational Citizenship Behavior – A Field Study on Azal Pharmaceutical Company – - Mohammedan, Hosamalden Abdalziz Moustafa (Journal of Economic, Administrative and Legal Sciences, 2021)
The study dealt with the impact of psychological empowerment in its dimensions (the importance of work, efficiency, independence, and influence) in achieving organizational citizenship behavior in Azal for the pharmaceutical industry, as the problem of the study was that business organizations were not interested in the psychological empowerment of workers, which affected the interest of individuals to take on the additional roles that come From organizational citizenship behavior. The study aimed to identify the impact of applying psychological empowerment in its dimensions (work significance, efficiency, independence, and influence) on achieving organizational citizenship behavior in Azal Pharmaceutical Industry. The importance of the study lies in the expected addition by presenting and testing a model of the relationship between psychological empowerment and organizational citizenship behavior. The main hypothesis has been tested: There is a statistically significant relationship between psychological empowerment in its dimensions (work importance, efficiency, independence, and influence) and the organizational citizenship behavior of the company in Azal Pharmaceutical Industry. The study is based on the descriptive and analytical approach as it describes the variables associated with the study and describes the characteristics of the study sample’s vocabulary. The basic community consisted of (560) and a selected sample was chosen from all workers, where the sample size was (228) individuals. The results of the study demonstrated the impact of psychological empowerment in its dimensions (the importance of work, efficiency, independence, and influence) in achieving organizational citizenship behavior, that after the influence of the variables that have the most impact on organizational citizenship, the reason is that the individual who feels a high level of influence has the ability to move More than just performing the work required. The study recommended the necessity for the company to invest in the nature of the influence relationship between psychological empowerment and organizational citizenship behavior and to explore the best skills and methods to invest this relationship and to reflect the skills that the dimensions of psychological empowerment impart in refining organizational citizenship behaviors. The work and roles performed by the individual on the one hand, and the beliefs, values and behaviors on the other hand.